Comparing the Effectiveness of Human Extracted Teeth and Plastic Teeth in Teaching Dental Anatomy - Noora Helene Thune; Anna Tostrup Kristensen; Amer Sehic; Julie Marie Haabeth Brox; Tor Paaske Utheim; Hugo Lewi Hammer; Qalbi Khan (Dentistry Journal)
Objectives: A thorough knowledge of tooth morphology, encompassing the detailed structural complexities, is essential for the practice of dental hygienists in all aspects of their profession. The aim of this study was to assess the efficacy of two instructional approaches in tooth morphology education, by analyzing the performance of dental hygienist students trained with human extracted teeth compared to those educated with plastic teeth models. Methods: This study included two cohorts of undergraduate dental hygienist students: a control group (n = 27) trained using human teeth, and an experimental group (n = 34) trained using plastic teeth models. Each group underwent two consecutive practical exams where they identified all 32 permanent teeth and 8 deciduous molars. Initially, students were tested on the training material that they were assigned (either extracted human teeth or plastic teeth), and, subsequently, they were tested using the alternative material. Both the number and patterns of identification errors were recorded and analyzed. Paired t-tests were used to compare error rates between real and plastic teeth for students trained on either plastic or real teeth, unpaired t-tests were conducted to assess differences in performance between students trained on plastic versus real teeth when tested on both tooth types, and Fisher’s exact tests were employed to examine variations in error proportions across maxillary and mandibular tooth categories. Results: The control group recorded a mean of 6.41 errors per student (total of 173 errors), with three students (11.1%) failing by committing over 12 errors. Their performance improved to a mean of 5.44 errors (total of 147 errors) when tested on plastic teeth, although the improvement was not statistically significant (p = 0.20). Conversely, the experimental group demonstrated high accuracy on plastic teeth, with 19 out of 34 students (55.9%) achieving perfect scores and a total of only 50 errors (mean, 1.47). Their performance, however, declined when tested on real teeth, escalating to a total of 354 errors, with 32 students (94.12%) making more errors on real teeth than on plastic, resulting in a significant increase in errors to an average of 10.41 per student (p < 0.001). Conclusions: This study demonstrates that students perform best when tested on the materials that they initially were trained with, showing that real teeth provide better educational outcomes than plastic models. This advantage underscores the importance of using natural teeth when learning dental anatomy.